Application of Symmetry Properties on the Hybrid Method in Time Domain - Yu Guo, Wei Wang, Ting Chen, Xiaowang Tong (Forest Chemicals Review, 1970)
Compared with the frequency-domain method, the time-domain method requires more storage space and computation in the hydrodynamic calculation of ships and marine structures. Establish a hybrid boundary integral equation coupled with Rankine source method and time-domain Green function method, solutions on the control surface were satisfied the far-field radiation condition with Rankine source method. According to the hybrid boundary model, the parts of time-domain Green function were only contained on the control surface. So this paper choose a hemispherical surface with symmetry property as a control surface, which could derivate a symmetric hybrid boundary integral equation easily to accomplish efficiently computation of floating body’s hydrodynamics. The proposed method is applied to calculate the hydrodynamic coefficients of the hemispheres with analytical solutions, and good agreement is obtained when are compared with the hydrodynamic coefficients in the frequency domain. The results show that the proposed method has high accuracy in the calculation of hydrodynamic coefficients of floating bodies in time domain, and can save storage space and improve the calculation speed to a certain extent.